Comparison of Dynamic Contrast-Enhanced 3T MR and 64-Row Multidetector CT Angiography for the Localization of Spinal Dural Arteriovenous Fistulas - Oda, S.; Utsunomiya, D.; Hirai, T.; Kai, Y.; Ohmori, Y.; Shigematsu, Y.; Iryo, Y.; Uetani, H.; Azuma, M.; Yamashita, Y. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: For the localization of spinal dural arteriovenous fistulas, it is not determined whether dynamic contrast-enhanced MRA is more reliable than multidetector CTA. The aim of this study was to compare the agreement between intra-arterial DSA, dynamic contrast-enhanced MRA at 3T, and 64-row multidetector CTA for the localization of spinal dural arteriovenous fistulas. MATERIALS AND METHODS: We enrolled 12 consecutive patients (11 men, 1 woman; age range, 46–83 years; mean, 65 years) who underwent preoperative dynamic contrast-enhanced MRA at 3T and 64-row multidetector CTA. The spinal dural arteriovenous fistula location was confirmed by intra-arterial DSA as the reference standard. Two reviewers independently evaluated the level of the artery feeding the spinal dural arteriovenous fistula on the basis of continuity between the feeder and abnormal spinal vessels on 3T dynamic contrast-enhanced MRA and 64-row multidetector CTA images. Interobserver and intermodality agreement was determined by calculation of the κ coefficient. RESULTS: On DSA, the vessel feeding the spinal dural arteriovenous fistula was the intercostal artery (7 cases), the lumbar artery (3 cases), and the internal iliac artery or the ascending pharyngeal artery (1 case each). For the fistula level, interobserver agreement was excellent for 3T dynamic contrast-enhanced MRA (κ = 0.97; 95% CI, 0.92–1.00) and very good for 64-row multidetector CTA (κ = 0.84; 95% CI, 0.72–0.96). Intermodality agreement with DSA was good for 3T dynamic contrast-enhanced MRA (κ = 0.78; 95% CI, 0.49–1.00) and moderate for 64-row multidetector CTA (κ = 0.41; 95% CI, 0.020–0.84). CONCLUSIONS: For the localization of spinal dural arteriovenous fistulas, 3T dynamic contrast-enhanced MRA may be more reliable than 64-row multidetector CTA. DCEdynamic contrast-enhancedSDAVFspinal dural arteriovenous fistulasVRvolume-rendering64-CTA64-row multidetector CTA